Photovoltaic potential in the Subarctic region ... : Фотоэлектрический потенциал в субарктическом регионе ... - Deng, Yuanbiao; Davydov, Vadim (St. Petersburg State Polytechnical University Journal. Physics and Mathematics, 2024)
With the world's policy support for solar energy and other renewable energy sources, solar photovoltaic technology has seen rapid development.However, from Saint Petersburg’s perspective, generating solar Photovoltaic (PV) energy in a Subarctic setting is hindered by several challenges, which diminish the enthusiasm for its adoption. Our work demonstrates that St. Petersburg is capable of generating more solar photovoltaic energy in summer than Central Europe, East Asia, and Southeast Asia. This finding could enhance our understanding of the seasonal and annual potential of solar PV energy in Subarctic region. ... : Благодаря государственной поддержке солнечной энергии и других возобновляемых источников энергии в мире, солнечная фотоэлектрическая технология быстро развивается. Однако с точки зрения Санкт-Петербурга, производство солнечной фотоэлектрической (PV) энергии в субарктическом регионе сопряжено с рядом трудностей, которые снижают интерес к её внедрению. Наша работа показывает, что Санкт-Петербург способен производить больше солнечной фотоэлектрической энергии летом, чем Центральная Европа, Восточная Азия и Юго-Восточная Азия. Это открытие может улучшить наше понимание сезонного и годового потенциала солнечной энергии в Субарктическом регионе. ...